Identifikasi Jenis dan Kepadatan Sampah Laut di Pantai Melon Kabupaten Selayar - Isman, Muh; Noor, Rahmat Januar; Afdal, Muh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
The presence of marine debris in the waters can change the quality of the waters, which is caused by anthropogenic activities. This marine debris is a persistent solid material, which is intentionally or unintentionally thrown away and left in the marine environment. This research aims to determine the type and density of marine debris. The research was carried out in August 2022 at Melon Beach, Selayar Regency. The research uses a descriptive quantitative approach by conducting field surveys. Data analysis uses descriptive techniques to classify the types of marine waste collected and calculate the density and mass of the waste. The research results showed that there were 27 types of macro waste and 5 types of micro waste. The density of plastic waste ranged from 3-6 items/m2, whereas in this study the density of plastic waste ranged from 0.0001-0.008 items/m2.